If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -8(x + 9) = 2 + -1(x + 9) Reorder the terms: 2x + -8(9 + x) = 2 + -1(x + 9) 2x + (9 * -8 + x * -8) = 2 + -1(x + 9) 2x + (-72 + -8x) = 2 + -1(x + 9) Reorder the terms: -72 + 2x + -8x = 2 + -1(x + 9) Combine like terms: 2x + -8x = -6x -72 + -6x = 2 + -1(x + 9) Reorder the terms: -72 + -6x = 2 + -1(9 + x) -72 + -6x = 2 + (9 * -1 + x * -1) -72 + -6x = 2 + (-9 + -1x) Combine like terms: 2 + -9 = -7 -72 + -6x = -7 + -1x Solving -72 + -6x = -7 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -72 + -6x + x = -7 + -1x + x Combine like terms: -6x + x = -5x -72 + -5x = -7 + -1x + x Combine like terms: -1x + x = 0 -72 + -5x = -7 + 0 -72 + -5x = -7 Add '72' to each side of the equation. -72 + 72 + -5x = -7 + 72 Combine like terms: -72 + 72 = 0 0 + -5x = -7 + 72 -5x = -7 + 72 Combine like terms: -7 + 72 = 65 -5x = 65 Divide each side by '-5'. x = -13 Simplifying x = -13
| 71=5d+6 | | 3n+7=31 | | x^2-40x-500=0 | | 2x-8(x-9)=2-(x+9) | | 2x=4(x+5) | | 8+2(4x-6)=5-4(2x+1) | | x^2+x/2-3 | | 97-5x=13x+23 | | 2(x+6)=5x+9-3x+3 | | 2(8s+5)-6s=2(5s+5)-13 | | 2(3x+4)=44 | | 8+6y=6(3+y) | | p=100-3q^2 | | 3x-8=3(x+5) | | 5c+3-4c= | | x^2+6x^2-32=0 | | 3(x+8)-24=3x | | 1/2n+(n-8)=25 | | 6(x-3)= | | b+10-5= | | x-4/9=576 | | 3x-2x+6=25-4x-8 | | x+x+5+2x=431 | | -2x=2x^2-14 | | x/4/9=576 | | 3(x-10)+5(x+2)=0 | | 17a+1b-7a+3b+17= | | 2x^3-x^2-25x-25=0 | | x-3/x=9/10 | | x-5/3-1=x-1/2 | | 5y(5y-9)=22 | | 9/16=9/2x |